Phylogenetic relationships and classification of the Malagasy pseudoxyrhophiine snake genera Geodipsas and Compsophis based on morphological and molecular data - Glaw, Frank; Nagy, Zoltán T.; Vences, Miguel (Zootaxa, 2007)
Based on a specimen found at Montagne d'Ambre in northern Madagascar morphologically agreeing with Compsophis albiventris Mocquard, 1894, we report on the rediscovery of this enigmatic snake genus and species and its molecular phylogenetic relationships. Compsophis albiventris, considered to be the only representative of its genus and unreported since its original description, bears strong morphological similarities to species of Geodipsas Boulenger, 1896. A molecular phylogeny based on DNA sequences of three mitochondrial and nuclear genes (complete cytochrome b, fragments of 16S rRNA and c-mos) in Compsophis albiventris and three Geodipsas species corroborated close relationships between C. albiventris and Geodipsas boulengeri, and showed that the genera Compsophis and Geodipsas together form a monophyletic unit. Despite the general similarities, morphological data and chromatic features support the existence of two species groups, corresponding to Compsophis and Geodipsas. We consequently consider Geodipsas as a subgenus of Compsophis and transfer all species currently in Geodipsas into the genus Compsophis.